2021
DOI: 10.1371/journal.pone.0247189
|View full text |Cite
|
Sign up to set email alerts
|

Levels and socioeconomic correlates of nonmarital fertility in Ghana

Abstract: Childbirth outside marriage has several negative implications for the well-being of children, women, and families globally. In sub-Saharan Africa, however, the phenomenon appears to be under-studied. In this study, we examine the levels and socioeconomic correlates of nonmarital fertility in Ghana. Using pooled data from the 2003, 2008, and the 2014 Ghana Demographic and Health Surveys, logistic regression models were used in determining significantly predictive factors of nonmarital fertility. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 19 publications
(14 reference statements)
5
17
0
Order By: Relevance
“…Education is also one of the identified correlates of nonmarital fertility, and these studies submitted that the higher the level of education of a woman, the less likely she is to have a child outside of marriage. Specifically, a Namibian study reported that education has an inverse relationship with non-marital fertility (Upchurch et al 2002;Perelli-Harris and Gerber 2011;Pazvakawambwa et al 2014;Nyarko and Potter 2021), but other evidence, also from Namibia, shows that the relationship is not strong, although the focus of this other study was among teenagers (Chimere-Dan 1997). Further evidence also shows that the place of residence (rural/urban) is a correlate of non-marital fertility; it has been submitted that non-marital fertility is more likely to occur among unmarried women residing in rural areas compared to women in urban areas (Nyarko and Potter 2021).…”
Section: Literature Reviewmentioning
confidence: 70%
See 4 more Smart Citations
“…Education is also one of the identified correlates of nonmarital fertility, and these studies submitted that the higher the level of education of a woman, the less likely she is to have a child outside of marriage. Specifically, a Namibian study reported that education has an inverse relationship with non-marital fertility (Upchurch et al 2002;Perelli-Harris and Gerber 2011;Pazvakawambwa et al 2014;Nyarko and Potter 2021), but other evidence, also from Namibia, shows that the relationship is not strong, although the focus of this other study was among teenagers (Chimere-Dan 1997). Further evidence also shows that the place of residence (rural/urban) is a correlate of non-marital fertility; it has been submitted that non-marital fertility is more likely to occur among unmarried women residing in rural areas compared to women in urban areas (Nyarko and Potter 2021).…”
Section: Literature Reviewmentioning
confidence: 70%
“…Specifically, a Namibian study reported that education has an inverse relationship with non-marital fertility (Upchurch et al 2002;Perelli-Harris and Gerber 2011;Pazvakawambwa et al 2014;Nyarko and Potter 2021), but other evidence, also from Namibia, shows that the relationship is not strong, although the focus of this other study was among teenagers (Chimere-Dan 1997). Further evidence also shows that the place of residence (rural/urban) is a correlate of non-marital fertility; it has been submitted that non-marital fertility is more likely to occur among unmarried women residing in rural areas compared to women in urban areas (Nyarko and Potter 2021). Scholarly evidence on religion and non-marital fertility has been reported in a study of the spatial variations in non-marital fertility, and it has been reported that in places with significant religious traditions, women show higher propensities to have low levels of non-marital fertility (Klüsener 2015).…”
Section: Literature Reviewmentioning
confidence: 70%
See 3 more Smart Citations